Policing in the Pacific Islands - Watson, Danielle; Howes, Loene; Dinnen, Sinclair; Bull, Melissa; Amin, Sara N. (Palgrave's Critical Policing Studies, 2023)
"This book is extremely well timed. As the Blue Pacific engages with longstanding and emerging security challenges, law enforcement officials will be called upon to play a range of important roles to safeguard the lives and livelihoods of their communities. The authors present a wealth of knowledge resources to inform policy and practice in our region". Dr Tess Newton Cain, Project Lead, Pacific Hub, Griffith Asia Institute, Australia This open access book brings together insights into Pacific policing, conceptualising policing broadly as order maintenance involving the actions of multiple local, regional and international actors with sometimes competing and conflicting agendas. A complex and multifaceted endeavour, scholarship on this topic is relatively scarce and widely dispersed across diverse sources. It examines how Pacific policing is shaped by changing state-society relations in different national contexts and ongoing processes of globalisation. Particular attention is given to the plural character of Pacific policing, profound challenges of gender equity, changing dynamics of crime, and the prominence of transnational policing in resource and capacity constrained domestic environments. The authors draw on examples from across the Pacific islands to provide a nuanced and contextualised account of policing in this socially diverse and rapidly transforming region. Danielle Watson is Senior Lecturer and Research Training Coordinator in the School of Justice, Queensland University of Technology, Australia. Loene Howes is Senior Lecturer in the School of Social Sciences at the University of Tasmania, Australia. Sinclair Dinnen is Senior Fellow in the Department of Pacific Affairs at the Australian National University, Australia. Melissa Bull is Interdisciplinary Scholar and Director of Queensland University of Technology Centre for Justice,Australia. Sara N. Amin is Senior Lecturer and the Discipline Coordinator of Sociology at the University of the South Pacific, Fiji.